The first steamboat on the Mississippi - North, Sterling (Boston The Riverside Press Cambridge, 1962)
The author of this book has always loved boats and running water, and once built an experimental model of a boat powered by a little windmill geared to the screw propeller at the stern. So the book is full of interesting descriptions of the boats and is nice for children as well as for older people.
Keywords: Children Literature